ANALISIS KARAKTER ORANG TUA DI FILM TURNING RED GUNA MEMBANTU ORANG TUA DALAM PENGEMBANGAN POLA ASUHNYA TERHADAP PEMBENTUKAN KARAKTER ANAK USIA DINI - Ramadhani, Ambar Putri; Lestari, Widya; Putri, Nia Karmila; Karunia, Karunia; Hayati, Zalmi; Sofyan, Fuaddilah Ali (Jurnal Multidisipliner Bharasumba, 2022)
This research is entitled character analysis of parents in the film turning red to help parents in developing their parenting towards early childhood character building. This study aims to describe and analyze the characters of mei-mei parents who are useful for helping parents in developing their parenting patterns for the formation of early childhood characters in the Disney+ animated film "Turning Red". The results of this study were obtained by descriptive method as a research procedure to produce descriptive data in the form of overall exposure. The method used in this research is "content analysis". The main data source for this research is the animated film “Turning Red” which was shown on Disney+. Positive/healthy parenting is the treatment of parents to their children which can be recognized through the words and actions of parents that have a good impact on the development of the child's personality/independence. The family has an important role as the first socialization medium for children. This role makes parents responsible for the physical and mental development of a child.